Fluid-Structure Interaction of NREL 5-MW Wind Turbine - Abd-Elhay, Mohamed Sayed Elkady (AUC Knowledge Fountain, 2021)
Wind energy is considered one of the major sources of renewable energy. Nowadays, wind turbine blades could exceed 100 m to maximize the generated power and minimize produced energy cost. Due to the enormous size of the wind turbines, the blades are subjected to failure by aerodynamics loads or instability issues. Also, the gravitational and centrifugal loads affect the wind turbine design because of the huge mass of the blades. Accordingly, wind turbine simulation became efficient in blade design to reduce the cost of its manufacturing. The fluid-structure interaction (FSI) is considered an effective way to study the turbine's behavior when the air and the blade are simulated as one system. In the present study, NREL 5 MW wind turbine with a blade length of 61.5m long is selected as a reference turbine to apply the FSI. The FSI is performed using three commercial software. ANSYS Fluent is used for the Computational Fluid Dynamics (CFD) model. The Finite Element (FE) model is simulated by Abaqus. In order to link both models together and transfer the data between them, MPCCI software is used. The blade is subjected to flap-wise deflection, edge-wise deflection, and torsion. So, a 2-way coupling simulation is implemented to optimize the blade deformation to protect it from hitting the tower, mitigate the effect of cyclic loading, and prevent the blade stall. This study introduced two passive optimization methods: material Bend Twist Coupling (BTC) and blade root fixation. One of the achievements of this study is that it is considered the first FSI research implemented at the AUC. Also, running the FSI model with three different codes and linking between them was another challenge. Moreover, it is concluded from this research that the 2-way coupling gives more accurate results than the 1-way coupling, although it is complicated. Although the centrifugal force reduces the flap-wise deflection, it significantly impacts the blade twist angle. The used material BTC optimization method improved the blade torsion stiffness while the root fixation improved the longitudinal stiffness. The improvement in the blade protects it from fatigue loading and stall by reducing the peak-to-peak amplitude and twisting the blade to feather.